Phycobilins and Phycobiliproteins Used in Food Industry and Medicine - Mysliwa-Kurdziel, Beata; Solymosi, Katalin (Mini Reviews in Medicinal Chemistry, 2017)
Background: Open tetrapyrroles termed phycobilins represent the major photosynthetic accessory pigments of several cyanobacteria and some eukaryotic algae such as the Glaucophyta, Cryptophyta and Rhodophyta. These pigments are covalently bound to so-called phycobiliproteins which are in general organized into phycobilisomes on the thylakoid membranes. Objectives: In this work we first briefly describe the physico-chemical properties, biosynthesis, occurrence, in vivo localization and roles of the phycobilin pigments and the phycobiliproteins. Then the potential applications and uses of these pigments, pigment-protein complexes and related products by the food industry (e.g., as LinaBlue® or the so-called spirulina extract used as coloring food), by the health industry or as fluorescent dyes are critically reviewed. In addition to the stability, bioavailability and safety issues of purified phycobilins and phycobiliproteins, literature data about their antioxidant, anticancer, anti-inflammatory, immunomodulatory, hepatoprotective, nephroprotective and neuroprotective effects, and their potential use in photodynamic therapy (PDT) are also discussed.
Keywords: Antioxidant